Application of Geographic Information System in seismic hazard assessment for the Central Alborz, Iran - Mousavi, Seyed Ramzan (2013)
The assessment of the seismic hazard of the Central Alborz in Northern Iran, expressed in terms of strong ground-motion which is demonstrated using Geographical Information System (GIS) techniques. The inability of a single hazard study to meet the needs of users and to handle the uncertainties of such analyses, demands a more user friendly procedure. GIS technology provides facilities for seismic hazard assessment which permits users to see the geographical distribution of calculated effects from different viewpoints. GIS is a powerful tool which is potentially very useful in seismic hazard analysis, seismic risk assessment and seismic zonation studies. This study applied GIS and spatial modeling using different data sets such as Digital elevation models (DEM), topographic maps, century earthquake data, and geological maps to help establish the seismic hazard assessment and analyze the tectonic history of the Alborz area. A period of historic seismicity encompassing more than 2,000 years has been collected and used as the earthquake catalogue data for this study. GIS programs are used in this research to collect, manipulate, generate and analyze various data input to seismic hazard analysis. GIS based methodology is introduced to combine available information on seismicity, tectonics and strong ground-motion. The external computer programs applied in this work are linked to the GIS, adding flexibility and analytical capabilities to the seismic hazard procedure. The traditional probabilistic approach is modified to account for detailed regional variation of seismicity parameters. Seismic hazard computer program is examined whether it is able to perform hazard analysis interactively within the GIS environment to yield acceptable results. The methodology is flexible as regards the way input data for seismic source boundaries, regional focal depth, faulting orientation, and seismogenic parameters are implemented. The procedure is capable of handling further potential site-dependent and site-specific hazard analysis. In the proposed approach, GIS raster –based data models are used in order to model geographical features in a cell-based system. The cell- based source model proposed in this study provides a framework for implementing many geographically referenced seismotectonic factors in to seismic hazard modeling. Using GIS methods in this study, seismic source zones are delineated based on the relationship of the observed earthquakes with the tectonic manifestations of the geological units. Maps with seismic interpretation are produced as a tool to delineate seismic source areas, to study the completeness of the earthquake catalogue, to determine the seismic activity, and to define recurrence parameters for the source areas. Various maps representing different aspects of seismic hazard are calculated and presented in this study. Probabilistic seismic Intensity maps and probabilistic ground acceleration maps are calculated based on different assumptions regarding seismicity parameters, source to- site distance, and alternative seismic source zones. Subsequently, the uniform hazard spectra are calculated in some major cities of Central Alborz, and the effects of uncertainties in the calculated ground motion are studied.